APLIKASI ANDROID PANDUAN MERAWAT TERNAK BURUNG LOVEBIRD - Buhori Muslim; Desi Puspita; Rahmad Andika (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2021)
In this study, the aim of this study was to produce an application/software method for caring for Lovebird birds, the main basis of which was programming using Android, which was useful in making it easier to learn how to raise birds correctly. Because from the information & data collection through interviews and observations, the interest in keeping birds is very high and the method of raising livestock that is carried out by enthusiasts is still using the old method, which equates the maintenance method with raising ordinary livestock. In making software, the method of caring for lovebirds, apart from Android as the main base, Adobe Flash Professional CS6 software is used for animation, where the development method uses Rapid application development (RAD) because based on understanding RAD it is easier, more practical and has good research product development stages, according to the purpose of the research. Research has produced applications that according to researchers can help raise lovebirds and to measure the success of making this application, alpha testing has been carried out with the aim of testing the validity of the application product, which is carried out by system design experts, material experts, linguists and media experts. Through these various tests, applications have been produced that have distinctive values ​​so that they are suitable and applicable for raising lovebirds so that good and quality livestock products are produced, as shown by the validity of media experts with a value of 4.0, with a very good category. Next, the material expert gave an assessment of 3.5 good categories, the design expert gave a score of 3.63 and finally the linguist gave a score of 3.6. then based on the results of this test the total validity shows the resulting application is very feasible and valid to use.